Pelatihan Pencak Silat Di Desa Ciklapa Tahun 2022 - Rama Cipta Prasetia; Dwi Septian; Abdul Hafid (Pusat Riset dan Inovasi Nasional, 2022)
Thematic Real Work Lectures (KKN) are KKN whose activity programs focus on certain areas according to social problems and the direction of development policies implemented by certain regional governments. STKIP Darussalam Cilacap organizes a Real Work Lecture program using the thematic method. KKN-T is intended to develop a spirit of empathy and concern for problems that occur in society. work program with the theme